Executive functions in aphasia: A novel aphasia screening for cognitive flexibility in everyday communication. Issue 9 (20th October 2020) - Spitzer, L.; Binkofski, F.; Willmes, K.; Bruehl, S.
ABSTRACT: Besides language deficits, persons with aphasia can present with impairments in executive functions such as cognitive flexibility. Since these impairments can restrict communicative abilities, diagnostics for aphasia should include their assessment. However, tests of executive functions, including symptoms expressed in everyday communication, are lacking for aphasia. Thus, our aim was to fill this gap and study the basic psychometric properties of the novel Cognitive Flexibility in Aphasia Screening. For a pilot evaluation, 26 German patients were examined with tests for language and cognitive flexibility as well as the novel screening. Moreover, 20 non-aphasic persons conducted the latter. We performed a Receiver Operating Characteristic analysis to investigate specificity and sensitivity, and multidimensional scaling to examine similarities between the screening and language/cognitive skills. We found good specificity and sensitivity and showed that the screening is correlated with language skills and verbal cognitive flexibility, revealing promising construct validity and feasibility of the new screening.